2009
DOI: 10.1111/j.1365-2125.2009.03386.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo glucuronidation of midazolam in humans

Abstract: Keywords 1′-hydroxymidazolam, 4-hydroxymidazolam, glucuronidation, in vitro metabolism, in vivo metabolism, midazolam ---------------------------------------------------------------------- Received WHAT THIS STUDY ADDS• N-glucuronide of midazolam has been quantified in human urine, indicating for the first time that this route of metabolism occurs in vivo.• Metabolism of 4-hydroxymidazolam has been compared with that of 1′-hydroxymidazolam in vitro.• This study provides further evidence, in vitro and in vivo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 29 publications
4
59
1
Order By: Relevance
“…The majority of glucuronidation reactions exhibited classical Michaelis- Menten kinetics; however, there were a few cases in which atypical kinetic profiles were found. There is growing evidence in the literature that UGT-catalyzed reactions, especially at high substrate concentrations, exhibit several different kinetic profiles (Iwuchukwu and Nagar, 2008;Hyland et al, 2009;Iwuchukwu et al, 2009;Aprile et al, 2010;Zhou et al, 2010), and our data are in agreement with these earlier reports. These atypical kinetic parameters indicate that, at higher concentrations, clearance by specific UGTs could be altered.…”
Section: Discussionsupporting
confidence: 83%
“…The majority of glucuronidation reactions exhibited classical Michaelis- Menten kinetics; however, there were a few cases in which atypical kinetic profiles were found. There is growing evidence in the literature that UGT-catalyzed reactions, especially at high substrate concentrations, exhibit several different kinetic profiles (Iwuchukwu and Nagar, 2008;Hyland et al, 2009;Iwuchukwu et al, 2009;Aprile et al, 2010;Zhou et al, 2010), and our data are in agreement with these earlier reports. These atypical kinetic parameters indicate that, at higher concentrations, clearance by specific UGTs could be altered.…”
Section: Discussionsupporting
confidence: 83%
“…As reported, erlotinib and panaxytriol, an active component in Shenmai injection (Zeng et al, 2013), both showed significant activation on MDZ 19-hydroxylation, whereas the activation but not inhibition made it difficult for the in vivo extrapolation. Moreover, either glucuronidation of hydroxylmidazolam or direct glucuronidation of MDZ occurs in vitro and in vivo (Klieber et al, 2008;Hyland et al, 2009;Seo et al, 2010). The multiple metabolic pathways may partly compensate for the decrease in MDZ metabolic clearance caused by the addition of the inhibitor and would also make it difficult for the in vivo quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam is a commonly used in vivo probe for CYP3A activity that undergoes CYP3A-mediated hydroxylation to form 1Ј-hydroxymidazolam and 4-hydroxymidazolam (Kronbach et al, 1989;Gorski et al, 1994). A small proportion, 1 to 2% of the dose, is glucuronidated (Hyland et al, 2009) and less than 1% of the administered dose is excreted unchanged in the urine. In contrast with other CYP3A substrates, midazolam does not appear to undergo P-glycoprotein-mediated transport (Schmiedlin-Ren et al, 1997;Kim et al, 1999).…”
mentioning
confidence: 99%